2022
DOI: 10.1186/s12941-022-00544-0
|View full text |Cite
|
Sign up to set email alerts
|

Third-generation cephalosporin resistant gram-negative bacteraemia in patients with haematological malignancy; an 11-year multi-centre retrospective study

Abstract: Objectives Among patients with haematological malignancy, bacteraemia is a common complication during chemotherapy-induced neutropenia. Resistance of gram-negative bacteria (GNB) to third-generation cephalosporins (3GC) is increasing. In order to explore the value of using surveillance cultures to guide empirical treatment e.g. choosing between carbapenem versus ceftazidime- we aimed to assess the distribution of pathogens causing bacteraemia in patients with haematological malignancy, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Among the microorganisms identified, an acquired resistance profile was found in 63% of the isolates, in agreement with recent studies that have shown a gradual increase in antimicrobial resistance; among the proposed mechanisms, selective pressure due to inadequate use of antibiotics has been considered [ 22 , 25 ]. In South Korea, Nham et al found a relationship between the development of BLEE-producing K. pneumoniae and the previous use of antimicrobials [ 20 ], without ruling out cross-bacterial transmission in different institutions, especially in those with low antimicrobial use, and the introduction of resistant bacteria from the community [ 26 ].…”
Section: Discussionsupporting
confidence: 86%
“…Among the microorganisms identified, an acquired resistance profile was found in 63% of the isolates, in agreement with recent studies that have shown a gradual increase in antimicrobial resistance; among the proposed mechanisms, selective pressure due to inadequate use of antibiotics has been considered [ 22 , 25 ]. In South Korea, Nham et al found a relationship between the development of BLEE-producing K. pneumoniae and the previous use of antimicrobials [ 20 ], without ruling out cross-bacterial transmission in different institutions, especially in those with low antimicrobial use, and the introduction of resistant bacteria from the community [ 26 ].…”
Section: Discussionsupporting
confidence: 86%
“…It is worth noting that given we only sampled 3GC-R K. pneumoniae isolates collected from bacteraemia infections, we are likely underestimating the true scope of transmission that could be occurring at our institution. Interestingly, transmission clusters almost exclusively were due to the ‘problem clones’ CG307 and CG29 (), and involved patients with haematological malignancy, likely because of the propensity of such individuals to develop bacteraemias following initial colonization [58]. Outbreaks of these two global problem clones have been described [59], although whether such transmission is happening due to direct human contact or being acquired from the hospital environment is not currently known.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, transmission clusters almost exclusively were due to the "problem clones" CG307 and CG29 (Fig. 4A) and involved patients with hematologic malignancy, likely because of the propensity of such individuals to develop bacteremias following initial colonization [59]. Outbreaks of these two "global problem clones" have been described [60] although whether such transmission is happening due to direct human contact or being acquired from the hospital environment is not currently known.…”
Section: Discussionmentioning
confidence: 99%